Morphological aspects of Sticholecitha serpentis (Plagiorchiida: Plagiorchiidae) in a new Viperidae host in the Brazilian Amazon - Chagas-De-souza, Darlison; Coêlho, Tássio Alves; Bassini-Silva, Ricardo [UNESP]; Ishiguro, Francisco Lazameth; Chalkidis, Hipócrates de Menezes; Viana, Lúcio André; Corrêa, Lincoln Lima (Universidad de Costa Rica, 2024)
Introduction: Sticholecitha serpentis is a poorly studied parasite of the snakes’ esophagus, with an unclear taxonomy. Currently, there are few records of S. serpentis in snakes in Brazil. Although it has been recorded in snakes of the family Viperidae, it has not yet been reported in Bothrops atrox. Objectives: To present new morphological characters, as well as ecological and parasitic relationships of S. serpentis with B. atrox. Methods: The samples were obtained in a dryland area in the Tapajós National Forest, Pará State, Brazil. Ten specimens of B. atrox were examined manually with the aid of tweezers, and three were positive for trematodes identified as S. serpentis in the oral cavity. Results: We provide scanning electron microscopy images, with detailed images of the S. serpentis tegument and its spines, as well as details of the dorsal keel using light microscopy methods. Moreover, we report the first record of S. serpentis parasitizing an Amazonian viperid, with infection frequency data of 30 %. Conclusion: We emphasize that the new morphological data presented in this manuscript provide additional information to facilitate the identification of this trematode in future studies.
Aspectos morfológicos de Sticholecitha serpentis (Plagiorchiida: Plagiorchiidae) en un nuevo hospedero de Viperidae en la Amazonia brasileña
Keywords: Bothrops atrox; new morphological aspects; snakes; Trematoda